2014
DOI: 10.5144/0256-4947.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes care and control: the effect of frequent visits to diabetes care center

Abstract: BACKGROUND AND OBJECTIVESFrequent visits to diabetes care clinics linked with better control of diabetes mellitus (DM), but debates exist about how frequently visits should be done. The objective of this study was to assess the effect of frequent visits on diabetes care and control.DESIGN AND SETTINGSA prospective study of 100 diabetic patients attending Prince Abdul-Aziz Bin-Majed Diabetes Care Centre (PAMDCC), Al Madinah Al Munawwarah, Saudi Arabia, during the period from March 2011 through December 2012.MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Also, the factors that lead to good glycemic control are multiple and complex . However, evidence suggests that frequent visits lead to better glycemic control . Among other reasons, it allows for better monitoring, early detection, and timely preventive care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the factors that lead to good glycemic control are multiple and complex . However, evidence suggests that frequent visits lead to better glycemic control . Among other reasons, it allows for better monitoring, early detection, and timely preventive care.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, evidence suggests that frequent visits lead to better glycemic control. 9,38,39 Among other reasons, it allows for better monitoring, early detection, and timely preventive care. Consequently, missed or delayed diabetes care and the resulting failure to manage the disease can lead to poor quality of life, expensive treatments, and loss of productivity, which in 2012 was estimated to total $245 billion.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with unsatisfactory glycaemic control, an association between visit frequency and better diabetes control has been shown in several studies [7][8][9][10]. According to a U.S. study, patients with T2D with relatively poor glycaemic control showed significant and clinically meaningful improvements in HbA 1c when contacted weekly by members of the health care system [7].…”
Section: Discussionmentioning
confidence: 98%
“…Recalling T2D dropouts is not necessary without problems. First, although there are former studies suggesting that more frequent contacts with the diabetes care centres predict better diabetes control [7][8][9][10] it is not known whether this is true also among the previous dropouts with T2D. Further, we do not know whether this intervention leads to increased use of the T2D care system by those patients gaining the most from it.…”
Section: Introductionmentioning
confidence: 92%
“…Patients who visited the health facility 1-4 times/year were 2.36-fold more likely to have glycemic control than those who visited the health facility >10 times/year, after controlling for potential confounders (P<0.001). This may be attributed to uncontrolled hyperglycemia that leads to an increased number of visits or the quality of these visits not meeting the patient's therapeutic needs ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%